121. Automated planning for Hodgkin lymphoma radiotherapy. (December 2018) - Oliviero, C.; Clemente, S.; D'Avino, V.; Palma, G.; Liuzzi, R.; Conson, M.; Pacelli, R.; Cella, L.
Abstract: Purpose: Purpose of the present study was to report on the evaluation of Pinnacle 3 Auto-Planning (AP) algorithm for Hodgkin lymphoma (HL) radiation therapy (RT). Methods: Planning CT-scans of 10 female patients with supradiaphragmatic HL were considered. Involved site clinical target volume (CTV) included the upper mediastinal and supraclavear nodes. Planning Target Volume (PTV) was obtained by CTV uniform 10-mm expansion. A total dose of 30 Gy was prescribed in 20 fractions. A "butterfly" (BF) volumetric modulated arc therapy was planned with Pinnacle3 v. 9.10 using SmartArc module and Collapsed Cone Convolution Superposition algorithm dose calculation. Human-driven (Manual-BF) and AP-BF optimization plans were generated using published priority and constraints on the OARs. In addition to BF technique, the AP engine was applied to a 2 coplanar disjointed arches (AP-ARC) technique. A single AP optimization list of PTV/OAR clinical goals was created for each patient. For plan comparison, DVHs of PTVs and OARs were extracted; homogeneity and conformity indices (HI and CI) computed and OARs dose-volume constraints and NTCP models for RP, HT, and CD evaluated. Non-parametric Friedman and Dunn tests were used to identify significant differences between groups. Results: AP (AP-BF or AP-ARC) offers comparable coverage of the PTV as the manual plan and a consistently better sparing of OARs. In particular, the heart and thyroid mean doses and lung V20 were significantly reduced using AP engine. Accordingly, AP provides similar, if not lower, complication risks. The median number of monitor units was slightly reduced by AP (3.5%). Hands-on planning time decreased on average by a factor of 3 by AP. Conclusions: The AP module was able to limit heart and thyroid complication risks, producing clinically acceptable HL plans with stable quality without additional user input. Overall AP-ARC provided better results in terms of OAR sparing when compared with AP-BF.